Programmes and calls for public health research in European countries - Conceição, Claúdia (2013)
Introduction: Public health research, at population and organizational level, needs to be identified independently within 'health' research from biomedicine and life sciences. In PHIRE (Public Health Innovation and Research in Europe), we investigated the extent and character of public health research calls and programmes in European countries. METHODS: Country respondents, identified through national member associations of the European Public Health Association completed a standardized recording instrument. Public health research was defined, and the call period limited to the latest full year (2010). Of the 30 countries included (EU 27 plus Iceland, Norway and Switzerland), there were reports for 25 countries A simple classification of the calls was developed. RESULTS: There were 75 calls and programmes included. Of these, 41 (55%) together were in France and the UK, and 34 in a further 14 countries, while 9 countries reported there were no calls or programmes opened in 2010. Calls were categorized across diseases, behaviours, determinants, services and methodologies. Some calls were broad, while others-particularly in the countries with several calls-were more detailed towards specific issues. Levels of funding varied markedly and were difficult to define. Where stated, in 32 responses, 19 calls were only open to national applicants and 13 from abroad. CONCLUSIONS: Most European countries have competitive programmes and calls relevant for public health research, but they are poorly identified. Only a minority of countries present a wide range of topics and specific fields. Effort is needed to develop classifications for public health programmes and calls for public health research, improve information (including financial) collection to enable systematic comparisons and build greater recognition of public health research within research communities, with national and European research funding organizations, and for practitioners and policymakers.